The effect of NaClO and EDTA pretreatment on the shear bond strength between the enamel white spot lesions and resin composite: An in vitro study - HE Jingyu, DING Yu, YANG Yuanyuan, NI Ke, WANG Yan, MENG Jian, MENG Qingfei (Kouqiang yixue)
Objective To compare the impact of NaClO and EDTA pretreatment on the enamel surfaces pore exposure rate, resin infiltration effectiveness and shear bond strength between the enamel white spot lesions (WSLs) and resin composite. Methods A total of 104 sound premolars were selected for the study. 4 mm×4 mm×2 mm enamel blocks from 64 sound premolars were cut in the center of the buccal surfaces of the teeth. All blocks were randomly divided into five groups: group SE(sound enamels as negative control); group DE(enamel blocks demineralised as positive control); group RI(resin infiltration); group N/RI(5.25% NaClO pretreatment and resin infiltration) and group E/RI(17% EDTA pretreatment and resin infiltration). The pore exposure rate of enamel surfaces and resin penetration depths were observed by scanning electron microscopy(SEM) and confocallaser scanning microscopy(CLSM) in each group. The remaining 40 premolars were cut from the cervical roots and the residual crowns were embedded in self-condensing resin material(buccal surfaces of the enamel exposed only). According to the grouping information, the samples were given the corresponding pretreatments and resin infiltration respectively and were bonded with a cylindrical resin cylinder on the buccal enamel surface for shear bond test. The shear bond strength and fracture modes were recorded and analyzed in each group. Results Compared to group RI, the pore exposure rate of the enamel surface, resin penetration depths, and percentage of resin penetration area in the N/RI and E/RI groups were significantly increased(P<0.05). The shear bond strength of the samples in group SE was the highest, and the lowest in group DE. Compared to group DE, the shear bond strength in groups RI, N/RI, and E/RI was significantly increased(P<0.05). Conclusion Enamel surface pretreatment with 5.25% NaClO or 17% EDTA has been demonstrated to effectively enhance the enamel pore exposure rate, resin penetration depth and the shear bond strength between WSLs and resin composite.